Teknik Pengenalan Suara Musik Pada Robot Seni Tari - Indra Dwisaputra; Ocsirendi Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
The dancing robot has become an annual competition in Indonesia that needs to be developed to improve robot performance. The dancing robot is a humanoid robot that has 24 degrees of freedom. For 2018 the theme raised was